Molecular Characterization of Vancomycin-Resistant Enterococcus spp. from Clinical Samples and Identification of a Novel Sequence Type in Mexico - Raúl Alejandro Atriano Briano; Nallely S. Badillo-Larios; Perla Niño-Moreno; Luis Fernando Pérez-González; Edgar A. Turrubiartes-Martínez (Antibiotics)
Background:Enterococcus spp. is the third leading cause of healthcare-associated infections in the American continent, often because of the virulence factors that protect the bacterium against host defenses and facilitate tissue attachment and genetic material exchange. In addition, vancomycin, considered a last-resort treatment, has shown reduced efficacy in Enterococcus spp. strains. However, the relationship between bacterial resistance and virulence factors remains unclear. This study intends to evaluate the prevalence of glycopeptide-resistant genotypes and virulence factors in Enterococcus spp. strains. Methods: Over six months, 159 Enterococcus spp. strains causing nosocomial infections were analyzed. Multiplex PCR was performed to identify species, glycopeptide-resistant genotypes, and 12 virulence factors. Results: The most abundant species identified were Enterococcus faecalis and E. faecium. Vancomycin resistance was observed in 10.7% of the isolates, and the vanA genotype was present in 47% of resistant samples. The main virulence factors detected were acm (54%), which is related to cell adhesion; gel E (66%), a metalloproteinase linked to tissue damage; and the sex pheromones cpd (64%) and ccf (84%), which are involved in horizontal gene transfer. A significant association was found between the prevalence of acm, ccf, and cpd in VRE isolates, indicating the potential dissemination of genes to emerging strains via horizontal gene transfer. In addition, a new E. faecium, which displayed five virulence factors and harbored the vanA sequence type, was identified and registered as ST2700. Conclusions:Enterococcus faecalis and E. faecium are clinically critical due to multidrug resistance and virulence factors like acm, which aids host colonization. Genes ccf and cpd promote resistance spread via horizontal transfer, while the emerging ST2700 strain requires urgent monitoring to curb its virulent, drug-resistant spread.